Relationship between informal learning, management support and career development among senior police officer at Bukit Aman Police Headquaters - Hj. Abdul Halim, Abu Hazwan (2021)
Career development practice is essential effort that recognizes employee as a vital organizational resource. Organizations belived that career development can improve the quality of their business strategy in the competitive and global business environment. Therefore, the study is designed to identify relationships between informal learning activities and career development. Career Development Practices organization utilized from the Juhary Career development dimension (2002) i.e. career planning and career management. Besides that, the study also used the theory of informal Learning activities Lohman (2006) to test the level of involvement of respondents in informal learning thus seeing the relationship between the two variables. The study involved a total of 191 respondents from 220 of the population which consisted of senior officers from the police headquarters in Bukit Aman. The quantitative approach was applied and simple random sampling techniques was used to identifying and distributing questionnaires to the respondents. Social Science statistics (SPSS) package version 23.0 was applied to perform descriptive analysis such as mean, frequency and standard deviation and inferential statistical methods (correlation and multiple regression) in the study. The findings found that there was a significant relationship at the moderate level between informal learning, management support and career development. Based on research, recommendations to the organization to perform career activities to improve the conduct of employees and career development practices in the organization. Also, recommendations for advanced study can be done on a larger scale and involve both the public and private sectors to compare the results of the study gained